The hills have eyes - Aja, Alexandre (Madrid Twentieth Century Fox, 2005)
A suburban American family is being stalked by a group of psychotic people who live in the desert, far away from civilization.
Ted Levine, Kathleen Quinlan, Dan Byrd
No recomendada a menores de 7 años
Idiomas : Inglés
Keywords: Películas cinematográficas -- DVD